Topspin generation in tennis - Cross, R. (Sports Engineering, 2019)
Tennis players impart topspin to the ball by striking the ball in an upwards direction while the racquet head itself is aligned with the string plane approximately vertical. Significantly larger spin can be generated if the racquet head is tilted forward. The amount of spin that can be generated was investigated by measuring the spin off a stationary hand-held racquet, and then calculating the effects of swinging the racquet towards the ball with the racquet head tilted forward. The trajectory of the ball was also calculated to ensure that the resulting spin was consistent with realistic values of the outgoing speed and angle of the ball.